Accelerated partial breast irradiation with interstitial multicatheter brachytherapy after breast-conserving surgery for low-risk early breast cancer. (August 2020) - Rodriguez-Ibarria, Nieves G.; Pinar, Ma Beatriz; García, Laura; Cabezón, M. Auxiliadora; Lloret, Marta; Rey-Baltar, Ma Dolores; Rdguez-Melcón, J. Ignacio; Lara, Pedro C.
Abstract: Patients with low-risk invasive ductal carcinoma treated with breast-conserving surgery (BCS) were included in a multicatheter brachytherapy APBI protocol. The primary endpoint was ipsilateral breast recurrence. Between December 2008–December 2017, 186 low-risk breast cancer patients were treated with APBI using interstitial multicatheter brachytherapy and followed prospectively. At 5-years of follow-up, cumulative local recurrence (LR) and cause-specific survival was 1.1% (95% CI 0.3–1.9) and 98.3% (95% CI 97.3–99.3%) respectively. No grade 3 adverse effects were observed. Postoperative APBI using multicatheter brachytherapy after BCS in early breast cancer patients have excellent rates of local control and survival, without significant toxicity. Highlights: Low risk early breast cancer patients have low rate of recurrences. APBI with interstitial multicatheter brachytherapy in low risk early breast cancer patients have excellent rates of local control and survival. Reducing time of treatment. Reducing adverse effects.